Pemilihan Prioritas Pengolahan Sampah dalam Perspektif Pengetahuan Masyarakat Untuk Reduksi Emisi - Sari, Novia; Rahmayanti, Henita; Sumargo, Bagus (Rekayasa, 2023)
Jakarta, as one of the metropolitan cities in Indonesia, has various problems in the waste sector. According to the 2022 National Waste Management Information System (SIPSN), daily waste generation in DKI Jakarta in 2022 is 8,527.07 tons with a reduction of around 26% in each administrative city area. This research uses literature studies based on several theories and research regarding waste problems with the aim of increasing community participation in implementing Minister of the Environment Regulation Number 13 of 2012 concerning Guidelines for Implementing Reduce, Reuse, Recycle through Waste Banks as an effort towards a circular economy. The results of the analysis using the Analytic Hierarchy Process (AHP) method with the help of the Superdecision Application show the weight of the criteria for determining waste processing in order from highest, namely showing that social aspects have the highest preference (51.49%), environmental aspects (28.24%), economic aspects (11.89%) and technological aspects (8.37%). Meanwhile, the alternative priority order with the highest preference is Compost at 51.617%, followed by the Recycle method at 24.40%, Incineration at 15.61% and the Landfill method at 8.36%. with an Inconsistency value of 0.02. This shows that the calculation of these criteria still falls within the inconsistency threshold, which cannot be more than 0.1.